Development Of Interactive Multimedia-Assisted Gamification Learning In The Innovation Management Course Class A13 - Puspitasari, Defita Aning; Setyosari, Punaji; Utami, Deka Dyah (Universitas Negeri Malang, 2024)
Gamification is still not familiar to students in class A13. This research aims to develop gamification learning development media assisted by interactive multimedia that can meet needs, feasibility and attractiveness. The types of data used in this research are quantitative and qualitative data. This research produces gamification assisted by interactive multimedia with PowerPoint class results. Based on validation tests carried out on media experts, material experts and students, it can be concluded that gamification learning media assisted by interactive multimedia is included in the valid category. So the gamification developed can be used in learning activities. Keywords: Learning Development, Gamification, Interactive Multimedia